Perbedaan Nilai Fraksi Ejeksi Ventrikel Kiri (LVEF) Pasien IMA-EST yang Menjalani Terapi Reperfusi dengan Fibrinolitik dan IKPP di RSUD Abdul Wahab Sjahranie Samarinda: Difference in Left Ventricular Ejection Fraction (LVEF) Value of AMI-EST Patients Underwent Reperfusion Therapy with Fibrinolytics and IKPP at Abdul Wahab Sjahranie Hospital, Samarinda - Annisa Fitri Fadhilah; Djoen Herdianto; Muhammad Khairul Nuryanto (Jurnal Sains dan Kesehatan, 2021)
Patients with Acute Myocardial Infarction with ST Segment Elevation (STEMI) should be given reperfusion therapy with fibrinolytic or PPCI (Primary Percutaneous Coronary Intervention) to prevent further myocardial damage. Currently PPCI is the main therapy choice for STEMI patients, but not all health facilities have these facilities. Thus, fibrinolytic may be the reperfusion therapy of choice in patients STEMI with chest pain onset ? 12 hours and without contraindications. STEMI can affect heart function, so the LVEF (Left Ventricular Ejection Fraction) value can be used to assess heart systolic function which can affect the prognosis of STEMI patients. The aim of this study was to identify the difference of LVEF values ??between STEMI patients undergoing reperfusion therapy with fibrinolytic and PPCI at Abdul Wahab Sajahranie Hospital, Samarinda. This study was an analytic observational study with a cross sectional design. The study population was all STEMI patients who undergoing reperfusion therapy with fibrinolytic and PPCI at Abdul Wahab Sjahranie Hospital, Samarinda for the period 2018-2019. Sampling was purposive sampling, with data sources derived from the patient's medical records. LVEF values ??were examined using transthoracic echocardiography, and Independent T-Test was used to analyze the difference of LVEF values ??between these groups. The result showed there was no significant difference in the LVEF value of STEMI patients undergoing reperfusion therapy with Fibrinolytics and PPCI (fibrinolytic 51.37 ± 12.254%, PPCI 56.47 ± 11.98%; p = 0.103 (p> 0.05)). Keywords: STEMI, Fibrinolytic, PPCI, LVEF